The use of instagram in coffee shop - Dharmayanti, Putu Devi; Darma, Gede Sri (International research journal of management, IT and social sciences, 2020)
The sophistication of technology such as smartphones that everyone had, it makes start-up entrepreneurs use it very well. The purpose of this study was to determine the effectiveness of the use of Instagram on the Coffee Shop "Ngocok Es Kopi".The results showed that the number of active users of the Instagram platform in Indonesia was dominated by 18-31 years old user groups. This is a strong reason for marketing Ngocok Es Kopi chose to use Instagram because the group is by market segmentation. The Instagram platform is very helpful for introducing products to consumers. Showing photos of the Ngocok Es Kopi products that look fresh and added with the eccentric tagline on the glass packaging, this gives a distinctive impression and makes potential consumers curious to try the product. Strategies are taken to increase the number of followers by giving them prizes in the form of discounts or free drinks on the condition that they have to follow the Instagram account of Ngocok Es Kopi, and give away by taking part in quizzes conducted by Ngocok Es Kopi.